Small Pointwise M-Projective Modules - Qaess Hussain, Mukdad (Iraqi Journal of Science, 2023)
Let R be a ring and let M be a left R-module. In this paper introduce a small pointwise M-projective module as generalization of small M- projective module, also introduce the notation of small pointwise projective cover and study their basic properties..